The Effectiveness of Constructed Wetland System Free Water Surface (FWS) with Substrate and Plant Variations in Reducing the Concentrations of Chromium in Water - Irawan Bagus Pratama - Nim: 10614007 , Rizky
Chromium wastewater is one type of waste that is often found in the environment as a result of various industrial activities. In general, the concentration of chromium produced by industries in Indonesia exceeds the threshold value which is a maximum range of 1 mg/L and is toxic to the environment and living things. A Constructed Wetland System is one approach that can be developed to remediate an environment contaminated with chromium waste. Several types of aquatic macrophytes are known to be effective as hyperaccumulators and some types of substrates can potentially be adsorbents. This study aims to determine the effectiveness of Constructed Wetland System Free Water Surface (FWS) using combinations of various substrate components and aquatic macrophytes to reduce chromium concentration in water. Chromium simulated wastewater with a concentration of 5,2 mg/L was exposed to seven systems, that is (1) a control which consists of wastewater without substrate and plants (K-A); (2) a control soilsawdust substrate without plants (K-TSK); (3) a control soil-zeolite sand substrate without plants (K-TPZ); (4) soil-sawdust substrate with Eichhornia crassipes (TSK-Ec); (5) soil-sawdust substrate with Ceratophyllum demersum (TSK-Cd); (6) soil-zeoilte sand substrate with Eichhornia crassipes (TPZ-Ec); and (7) soil-zeoilte sand substrate with Ceratophyllum demersum (TPZ-Ec). Chromium concentrations was measured 8, 16, 24, 32, 40, 48, 56, and 72 hours. The results after treatment showed a reduction efficiency 87,5%; 89,9%; 93,6%; 94%; 94,5%; 95% for K-TSK system, K-TPZ system, TSK-Ec system, TPZ-Ec system, TSK-Cd system and TPZCd system respectively, while the K-A system only decreased by 15,9%. The rate of chromium concentration reduction in the K-TSK system to the TPZ-Cd system ranges from 1,21 to 1,34%. The final chromium concentration in the K-TSK system to the TPZ-Cd system ranges from 0,2-0,61 mg/L, thus achieving the required quality standards. Based on these results it can be concluded that all systems except the K-A system are effective in reducing chromium concentration in water.